The characterization and stereochemistry of biosynthesis of dolichols in rat liver - Gough, Doreen P. (1970)
It was shown that rat liver contains a series of dolichols with chain lengths of from 17 (or possibly 16) to 21 isoprene residues, the main constituent of the mixture being dolichol-18. By using double-labelled radioactive mevalonates it was demonstrated that each of these dolichols possesses three biogenetically trans-isoprene residues and that the remaining residues are biogenetically cis, suggesting that these polyprenols are biosynthesized from all-trans-farnesyl pyrophosphate by the cis additions of isoprene residues, followed by saturation of the α-isoprene residue. The results obtained with these radioactive mevalonates also indicated that the activity of isopentenylpyrophosphate isomerase is low relative to the activity of prenyltransferase in rat liver.